Analisis Pengembangan Ekonomi Wilayah di Kabupaten Hulu Sungai Selatan - Dewi Siska (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2018)
Regional development is part of the efforts by a region to spur socio-economic development, including a lowering the inequalities that occur between regions and preservation of environmental sustainability in the region. The purpose of this paper is to explore the conditions of economic development in the area of Hulu Sungai Selatan District as one of the districts in the Kandangan Mainstay Area and its surroundings. The method used in this study is a descriptive method with a quantitative approach, based on secondary gathered from Statistical Bureau of Hulu Sungai Selatan Regency and is analysed using entropy. The results of the analysis show that the area is evenly distributed. The entropy analysis also shows that the Kandangan Subdistrict area is the most evenly distributed region and the Telaga Langsat Subdistrict area is the region with the most uneven activity intensity. Of the nine sectors that co-exist, the sector that is relatively evenly distributed in each region is the agriculture sector of rice and secondary crops, while the electricity, gas and clean water sector are the most uneven sector. However, the development conditions of the production activities of the 8 agricultural commodities of rice and secondary crops as a sector that is evenly distributed in each region, based on entropy analysis of its distribution in each region are relatively uneven. Keywords : Regional economic development, entropy analysis, mainstay area Abstrak Pengembangan wilayah merupakan bagian dari upaya suatu wilayah untuk memacu perkembangan sosial ekonomi, diantaranya penurunan kesenjangan yang terjadi antar wilayah dan pemeliharaan kelestarian lingkungan hidup di wilayah tersebut. Tujuan tulisan ini yaitu menggali kondisi pengembangan ekonomi wilayah Kabupaten Hulu Sungai Selatan sebagai salah satu kabupaten di Kawasan Andalan Kandangan dan sekitarnya. Penelitian ini dikaji secara deskriptif kualitatif dengan metode kuantitatif, berdasarkan data sekunder yang diambil dari BPS Kabupaten Hulu Sungai Selatan yang kemudian di analisis menggunakan analisis entropy. Hasil analisis menunjukkan pengembangan ekonomi wilayah berdasarkan anlisis entropy menunjukkan Kabupaten Hulu Sungai Selatan relatif merata. Hasil analisis entropy menunjukkan wilayah Kecamatan Kandangan sebagai wilayah dengan aktifitas paling merata dan wilayah Kecamatan Telaga Langsat menjadi wilayah dengan intensitas aktifitas paling tidak merata. Dari 9 sektor yang ada, sektor yang relatif merata di setiap wilayah adalah sektor pertanian tanaman padi dan palawija, sedangkan sektor listrik, gas, dan air bersih merupakan sektor yang paling tidak merata. Akan tetapi, kondisi perkembangan aktifitas produksi dari 8 komoditas pertanian tanaman padi dan palawija sebagai sektor yang relatif merata di setiap wilayah, berdasarkan analisis entropy penyebarannya di setiap wilayah relatif tidak merata.